KAJIAN EMPIRIS PENENTU NIAT BERWIRAUSAHA PADA MAHASISWA - Sugiantari, Ni Wayan Ayuk; Suasana, I. G. A. K. Gede (E-Jurnal Manajemen; Vol 5 No 6 (2016), 2016)
The purpose of this study to analyze the influence of need for achievement, family support and self-efficacy in entrepreneurship intentions mahaiswa D III Faculty of Economics and Business, University of Udayana. This research was conducted at the Faculty of Economics and Business, University of Udayana. The total sample of 75 students D III is already taking entrepreneurship courses, using non-probability sampling method in the form of purposive sampling. The analysis technique used is multiple regression and Analisys of Variance (ANOVA). Based on the analysis found that the variable need for achievement, and family support positive and significant effect on the intention of entrepreneurship students, while in the variable self-efficacy was found that self-efficacy positive effect was not significant to the intention of entrepreneurship and test one way ANOVA obtained no significant difference in average -rata intention of entrepreneurship based on both gender groups. Based on the research results is important for the Faculty of Economics and Business, University of Udayana as educational institutions to further improve and shape entrepreneurial spirit in students.
Keywords: need for achievement, family support, self-efficacy, gender and entrepreneurship intentions